Upaya Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Menggambar di Kelompok B2 TK Pertiwi Margorejo Tempel Sleman Tahun Pelajaran 2019/2020 - Titik Amini (Nusantara: Jurnal Pendidikan Indonesia, 2021)
developing fine motor skills, this is because children feel that motor activities are very boring, teachers do not use interesting/varied learning media and tools, provide guidance and motivation to children, good learning atmosphere. less fun and the teacher does not carry out development activities gradually, repeatedly and integratively in accordance with the development of children's fine motor skills. This type of research is Classroom Action Research, which uses two cycles with each cycle consisting of four stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. The subjects of this study were group B TK Pertiwi Margorejo Tempel Sleman with 15 children, consisting of 9 boys and 6 girls. The object of this research is an effort to improve children's fine motor skills through drawing activities. Data analysis was obtained through demonstration, performance, assignment, observation and documentation. The results of increasing fine motor skills through drawing activities in the first cycle of children who developed very well 71% increased to 85.43%. In the second cycle the fine motor skills of children who developed very well 50% increased to 93.71%..